2022
DOI: 10.1007/s00603-022-03018-z
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on Anisotropy and Shape Effect of Mechanical Properties of Columnar Jointed Basalts Containing Transverse Joints

Abstract: We studied the non-linear mechanical response and failure mechanism of columnar jointed basalts (CJBs) with transverse joints by modeling meso-mechanics, statistical damage theory and continuum mechanics. The anisotropy and shape effect of CJBs with transverse joints were captured under different lateral pressures. The digital images were transformed into heterogeneous element meshes, and the gradual fracturing process and various failure modes of CJBs were reproduced. The compressive strength (CS) and equival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…where σ 1 , σ 3 , ϕ and f c represents the major principal stress, minor principal stress, internal friction angle and uniaxial compressive strength, respectively. The damage-induced degeneration of element parameter can be computed according to Wang et al (2022) [28].…”
Section: Damage and Failure Of One Meso-elementmentioning
confidence: 99%
“…where σ 1 , σ 3 , ϕ and f c represents the major principal stress, minor principal stress, internal friction angle and uniaxial compressive strength, respectively. The damage-induced degeneration of element parameter can be computed according to Wang et al (2022) [28].…”
Section: Damage and Failure Of One Meso-elementmentioning
confidence: 99%
“…Considering that the shales, as a kind of heterogeneous materials, contain various granular media, holes, micro-cracks and other defects, their mechanical behaviours are closely related to the inner meso-structure, such as stress distribution, crack propagation, damage evolution and failure mode. The DIP-enhanced RFPA can effectively characterize the mesoscopic structure of the heterogeneous shales by processing digital image (Wang et al 2021(Wang et al , 2022b. Clearly, the grey value distribution of the image was analyzed, and the finite element mesh was divided using the pixels.…”
Section: Principal Of Numerical Proceduresmentioning
confidence: 99%
“…Many engineering practices have shown that rock joint shear slip is one of the key causes of rock mass engineering instability [ 3 , 4 ]. Full-length bolted support can effectively control shear slip deformation of the rock mass to realize stability control of rock mass, which has become one of the most widely used means in rock mass engineering reinforcement [ 5 , 6 , 7 , 8 , 9 , 10 ]. However, with increasingly complex engineering conditions, the failure of bolted support induced by rock joint shear slip becomes increasingly prominent.…”
Section: Introductionmentioning
confidence: 99%